Instructional Video Media Development in the Islamic Cultural History Subjects to Improve Junior High School Students' Comprehension and Academic Achievement - Makmunah, Jamilatul L.; Mariono, Andi; Dewi, Utari (Jurnal Penelitian Pendidikan Islam, 2022)
This study aims to test the effectiveness of one learning media, learning videos, on the subject of Islamic Cultural History (SKI). This research uses the research and development (R&D) method with ADDIE pretest-posttest control group design. The experimental subjects in this study were 58 class VIII SMP Al-Huda students, divided into an experimental class and a control class. The results showed that the media that had been developed was suitable for use in learning. Other findings from this study indicate an effect of using instructional videos on students' level of understanding. The mean score in the experimental group was much higher than in the control group. It proves that there is a difference in value between the experimental group and the control group. Learning video media in this subject has a positive impact on students, making students more enthusiastic and enthusiastic about learning.